Hypothermia but not the N-methyl-D-aspartate antagonist, MK-801, attenuates neuronal damage in gerbils subjected to transient global ischemia. - Buchan, A; Pulsinelli, W (1990)
Several laboratories have reported a significant reduction of ischemia-induced injury to hippocampal neurons in rodents treated with competitive and noncompetitive N-methyl-D-aspartate (NMDA) receptor-channel antagonists. This study examined the effects of the noncompetitive antagonist (+)-5-methyl-10,11-dihydro-5H-dibenzo[a,d]cyclohepten-5,10-imine maleate (MK-801) in Mongolian gerbils subjected to 5 min of bilateral carotid artery occlusion. In adult female gerbils, single doses of MK-801 injected 1 hr prior to ischemia significantly (p less than 0.01) reduced damage to CA1 hippocampal neurons. However, the drug rendered the postischemic animals comatose and hypothermic for several hours compared with the saline-treated animals. In subsequent experiments, animals pretreated with MK-801 and maintained normothermic during and after forebrain ischemia demonstrated no amelioration of hippocampal damage. Gerbils not treated with MK-801, but kept hypothermic in the postischemic period to approximately the same degree (34.5 degrees C) and duration (8 hr) as was induced by MK-801 therapy showed significant (p less than 0.01) protection of CA1 neurons against ischemia. The neuroprotective activity of MK-801 against transient global ischemia appears to be largely a consequence of postischemic hypothermia rather than a direct action on NMDA receptor-channels.